2019
DOI: 10.3889/oamjms.2019.627
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Estrogen Levels with Lipid Profile in Menopause Women in West Sumatera

Abstract: BACKGROUND:Menopause is a condition where women had not experienced menstruation for 12 consecutive cycles. At menopause period, there is alteration in women reproductive cycle where estrogen decreased and lipid status altered.AIM:This study is aimed to understand the association of estrogen level and lipid status in menopause women.METHODS:This study was an observational study with cross-sectional design underwent in Obstetrics and Gynecology Polyclinic Dr M. Djamil Hospital, Padang to examine estrogen level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…It was found that F. deltoidea restored the levels of total cholesterol, triglycerides, LDL-C, and HDL-C to normal levels in PCOS rats that had improvement in hormonal profile and the estrous cycle. The data support that the relationship between lipid profile and sex hormones [ 49 , 50 ]. These results are also compatible with earlier studies demonstrating that F. deltoidea can reverse the abnormalities in the lipid profile of diabetic rats [ 51 ] and adults with pre-diabetes [ 52 ],…”
Section: Discussionsupporting
confidence: 84%
“…It was found that F. deltoidea restored the levels of total cholesterol, triglycerides, LDL-C, and HDL-C to normal levels in PCOS rats that had improvement in hormonal profile and the estrous cycle. The data support that the relationship between lipid profile and sex hormones [ 49 , 50 ]. These results are also compatible with earlier studies demonstrating that F. deltoidea can reverse the abnormalities in the lipid profile of diabetic rats [ 51 ] and adults with pre-diabetes [ 52 ],…”
Section: Discussionsupporting
confidence: 84%
“…It also increases lipoprotein lipase activity, and lipoprotein lipase is responsible for hydrolyzing TG. 31 In males’, testosterone increases the degradation of HDL molecule by stimulating the expression of genes encoding for hepatic lipase and scavenger receptor B. On the other hand, testosterone reduced the expression of LDL receptors and the activity of lipoprotein lipase.…”
Section: Discussionmentioning
confidence: 99%
“…30 Besides, the reduction of estrogen causes dysregulation of lipoprotein lipase activity and results in to increase in LDL and TC levels. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Menopause is a time of drastic transition and many hormonal changes in women [ 89 ]. One of the major results of menopause is a marked decrease in estrogen levels [ 90 ]. The post-menopausal levels of triacylglycerols are much higher than the triacylglycerol levels in pre-menopausal woman [ 89 ].…”
Section: Molecular and Cellular Basis Of T2d Pathogenesismentioning
confidence: 99%